Architecture-based Evolution of Dependable Software-intensive Systems - Heinrich, Robert (The Karlsruhe Series on Software Design and Quality, 2023)
This cumulative habilitation thesis, proposes concepts for (i) modelling and analysing dependability based on architectural models of software-intensive systems early in development, (ii) decomposition and composition of modelling languages and analysis techniques to enable more flexibility in evolution, and (iii) bridging the divergent levels of abstraction between data of the operation phase, architectural models and source code of the development phase.